Dynamic response assessment in compliance with the Eurocodes for the elevated viaducts of the Doha Metro Green Line. (19th February 2017) - Ayoub, Essam; Mehanny, Sameh; Malek, Charles; Helmy, Gamal
Abstract : The double‐track elevated viaducts of the Doha Metro Green Line, which is currently under construction, are 2.7‐km long and consist of in situ and precast segmental simply supported spans ranging from 20 to 35 m and in situ two‐ and three‐span continuous (39.5–57, 50–51–44, and 37–68–37 m) U‐trough decks. The nontypical configuration of the continuous spans was imposed due to utilities and infrastructure requirements. All viaduct decks (in situ and precast) are posttensioned to minimize any concrete cracking. To ensure passenger comfort and traffic safety during train operation, performing a dynamic analysis was vital. The dynamic analysis focused on the vertical accelerations and vertical displacements. The actual train of the project, comprising six vehicles with a total length of 120 m and with actual axle loads (max. axle load = 160 kN, with four axles per vehicle), was adopted in the dynamic analysis. The analysis was carried out using both direct time integration of the equation of motion and modal time history analysis for different train speeds ranging from 60 km/hr to the maximum permissible speed along the metro line (160 km/hr). The maximum vertical accelerations and maximum vertical deflections were monitored for each train speed using the CSiBridge software used in the current project and compared with the allowable values given in EN 1991‐2 and EN 1990, Annex 2. According to relevant Eurocodes requirements, the vertical accelerations and the vertical deflections were found to be acceptable.